The Influence of Leadership Style and Position Promotion on Employee Performance at Uniqlo Sun Plaza Medan - Aldy Husaini Hutasuhut; Teguh Wahyono (Yayasan Multidimensi Kreatif, 2025)
This study aims to analyze the influence of leadership style and job improvement on employee performance at Uniqlo Sun Plaza Medan, this study uses associative and quantitative approaches, The population in this study is employees, which amounts to 33 people, the sampling technique used is quota sampling with all populations being sampled, the data analysis technique used is multiple linear regression analysis, The results of this study show that leadership significantly affects the performance of Uniqlo Sun Plaza employees because the t-value of the t-count > t table (2,669 > 2,039) and the significance level is 0.008 < 0.05, the increase in position significantly affects the performance of Uniqlo Sun Plaza employees because the t-value calculated > t table (3,689 > 2,039) and the significance level is 0.001 < 0.0, Based on the criteria of hypothesis testing, if it is >, it is rejected and accepted. This means that independent variables consisting of leadership (), position increase (), simultaneously have a significant effect on the performance of Uniqlo Sun Plaza Medan employeesF_hitung F_tabel H_0 H_1 X_1 X_2